How do Polish and Indonesian disclose in Facebook?: Differences in online self‐disclosure, need for popularity, need to belong and self‐esteem. Issue 3 (2014) - ,; ,
Abstract : Purpose – The purpose of this study is to explain cross‐cultural differences in online self‐disclosure (SD) between Indonesians, who live in a highly collectivist culture, and Poles – a hierarchical individualist culture. Various psychological factors have been taken into consideration, such as the need for popularity (NfP), the need to belong (NtB) and self‐esteem (SE).Design/methodology/approach – This study was designed as a quantitative study. First, a one‐way ANOVA was performed to compare online SD and specific behaviours online between Indonesians and Poles. Second, correlational analysis between online SD and other psychological factors (NfP, NtB, SE) was conducted.Findings – Indonesians were more likely than Poles to disclose information on Facebook. On the other hand, Poles showed a tendency to disclose more positive content than Indonesians. It was also found that SE was significantly correlated with positive content of online SD for both countries. Furthermore, online SD on Facebook is more closely associated with NfP than NtB.Research limitations/implications – This study possesses several limitations in regard to the lack of generalization; this is due to the choice in scales and the sampling procedure. Thereby, further studies must take into consideration the proportion of genders, the differences in the construction of the "self" between individualist and collectivist cultures and the interpretation of culture orientation based on the primary data. Furthermore, several results related to the online SD would need to be verified by further studies to get a holistic explanation.Originality/value – The current research is for all means and purposes original, as it investigates the differences of online behaviours between cultures – Polish and Indonesian – basing on the premise that there are crucial differences between collectivist and individualist cultures. No prior articles attempted the comparison between those nationalities in online behaviour.